Cancer Patients' Perception of Usefulness of Wearable Exercise Trackers. Issue 8 (20th October 2020) - Ng, Amy; Gupta, Ekta; Bansal, Swati; Fontillas, Rhodora C.; Amos, Charles E.; Williams, Janet L.; Dibaj, Seyedeh; Bruera, Eduardo
Abstract : Objective: To determine the feasibility and perception of usefulness of wearable trackers in inpatient and outpatient cancer rehabilitation patients. Design: Prospective study. Setting: Acute inpatient rehabilitation and outpatient clinic at a tertiary cancer center. Participants: Adult cancer patients (N = 100). Interventions: Participants were provided with wearable trackers for the duration of the study. Main Outcome Measures: Survey regarding feasibility (as defined as equal or more than two‐thirds of participants reporting use of the wearable tracker) and usefulness of the wearable tracker and Edmonton Symptom Assessment Scale (ESAS‐FS) in both inpatient and outpatient populations. Activity minutes, number of steps, heart rate, and sleep data were collected from the wearable tracker. Results: Patients reported the use of a wearable tracker is feasible, with 48/50 (96%) outpatients and 47/50 (94%) inpatients reported wearing the wearable tracker daily and 37/49 (76%) outpatients and 29/50 (58%) inpatients reported that they would continue to wear the wearable tracker after this study. The majority of cancer patients (41/49 [84%] of outpatient and 33/50 [66%] of inpatient patients) reported that the wearable tracker was useful and 41/49 (84%) outpatients and 27/50 (54%) inpatients perceived the wearable tracker as helping to increase physical activity. Conclusions: The use of wearable trackers in cancer patients is feasible and patients perceive wearable trackers as useful in both the inpatient and outpatient rehabilitation setting. Physical activity in these patients was better in the outpatient population, as expected because of less medical acuity.